Atypical Facial Pain: An Enigma in Diagnosis and Treatment- A case report - Acharya, Nisha; Karmacharya, Anu; Paudel, Durga; Murakami, Satoshi; Abiko, Yoshihiro (Journal of Nepalese Prosthodontic Society, 2025)
Atypical odontalgia (AO) is chronic orofacial pain condition characterized by the persistent orofacial pain that affects teeth or tooth socket after extraction in absence of any identifiable cause on clinical or radiographic examination. This causes a diagnostic dilemma for the clinician and is very frustrating to the patients. Patients demand treatments in a hope of pain relief and visit multiple clinics for the same. This leads to multiple unnecessary treatments without remission of the symptoms. These conditions are usually related to psychiatric, vascular or neurological problems. Hence, antidepressants like amitriptyline or serotonin-norepinephrine reuptake inhibitors (SNRIs) like duloxetine and antianxiety like ethyl loflazepate are reported to be effective in the treatment of AO. However, efficacy of such drugs varies among individuals and their symptoms. AO is a condition that carries sensory as well as complex psychological problems. Thus, while prescribing the drugs all the aspects including the variation in pharmaco-therapeutic responses should be considered. In this case report, we have reported a case of AO and have discussed its diagnostic workout, characteristic and the management aspect with combination of various medicines.